(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The study aims to investigate the correlations and impact between the independent variable (cloud accounting information systems) and the dependent variable (financial performance). It utilized a descriptive analytical approach to analyze the data, employing a questionnaire as the primary data collection tool. A total of 37 questionnaires were distributed to accountants and auditors at the Northern Technical University, with 35 returned. Upon review, it was determined that 4 questionnaires were unsuitable for analysis, resulting in 31 questionnaires suitable for analysis. The study drew several conclusions, notably identifying a correlation between cloud information systems and financial performance. Additionally, it provided recommendations, with a key suggestion being that government institutions should fully embrace cloud computing and its applications to enhance their operations and progress toward the future.